Identifying barriers to efficient cold chain management in the halal food industry - Mahamad Maifiah, Mohd Hafidz; Ahmad, Anis Najiha; Iskandar, Muhammad Affifuddin; E Azam, Md Siddique (Asian Scholars Network (ASNet), 2025)
The halal status of food products is verified by ensuring that the ingredients and processes involved do not impose any non-halal elements. In addition, the toyyiban aspect of a product which encompasses safety and good quality must always be preserved and maintained. This is especially important for halal perishable food products that are highly sensitive to temperature changes. Cold chain management of halal perishable foods throughout the supply chain is crucial to preserving product quality, integrity and safety. Otherwise, inefficiencies in cold chain management can significantly undermine the quality of the food products. The objectives of this research were to uncover the underlying barriers that influence the efficiency of cold chain management for halal food products and determine their differences in relation to the different profiles of companies. Structured questionnaires were disseminated among the identified halal-certified food businesses (n=102) in cold chain activities. Our analysis identified four barriers which are the human factor, financial implications, utility deficiencies, and procedural and management factor, which vary depending on the companies’ profiles. Strategies tailored to mitigate these barriers should be implemented, considering the unique characteristics and requirements of each company.